Point-prevalence survey of outpatient antibiotic prescription at a tertiary medical center in Sri Lanka: opportunities to improve prescribing practices for respiratory illnesses - Helen L. Zhang; Champica Bodinayake; Gaya B. Wijayaratne; Pasangi Jayatissa; D. L. Bhagya Piyasiri; Ruvini Kurukulasooriya; Tianchen Sheng; Ajith Nagahawatte; Christopher Woods; L. Gayani Tillekeratne (BMC Infectious Diseases, 2021)
Abstract Background Inappropriate antibiotic use is linked to the spread of antimicrobial resistance worldwide, but there are limited systemic data on antibiotic utilization in low- and middle-income countries. The purpose of this study was to evaluate the prevalence and patterns of antibiotic prescription in an ambulatory care setting in Sri Lanka. Methods This cross-sectional survey was conducted at the Outpatient Department of a public tertiary medical center in Southern Province, Sri Lanka from February to April 2019. Among consecutive outpatients presenting for care, questionnaires were verbally administered to a systematic random sample to capture information about patient demographics, illness characteristics, and visit outcomes. Prescription data were obtained from the outpatient pharmacy’s electronic prescribing system. Results Of 409 surveyed patients, 146 (35.7%) were prescribed an antibiotic. The most frequently prescribed agents were amoxicillin (41 patients, 28.1% of antibiotic recipients) and first-generation cephalosporins (38, 26.0%). Respiratory indications were the most common reason for antibiotic use, comprising 69 (47.3%) of all antibiotic prescriptions. Antibiotics were prescribed for 66.1% of patients presenting with cough and 78.8% of those presenting with rhinorrhea or nasal congestion. Among all antibiotic recipients, 6 (4.1%) underwent diagnostic studies. Conclusions A high prevalence of antibiotic prescription was observed, in particular for treatment of respiratory conditions. These data support the need for improved antimicrobial stewardship in the Sri Lankan outpatient setting.